Defence Engineering Companies Strategic Planning and Country’s Regional Development - Пингелов, Красимир (Научни трудове, 2020)
This report considers how Republic of Bulgaria territory is divided into administrative regions. It examines how Defence Industry Engineering Companies (DIEC) are geographically established and looks for patterns in their location and concentration. It analyses how the regional development and DIEC influence each other. It examines how this influence is taken into account when doing business strategic planning. The report makes an attempt to explain how this mutual influence changes the region’s and company’s competitiveness.